2006
DOI: 10.2353/ajpath.2006.051331
|View full text |Cite
|
Sign up to set email alerts
|

Shigatoxin-Induced Endothelin-1 Expression in Cultured Podocytes Autocrinally Mediates Actin Remodeling

Abstract: Shigatoxin (Stx) is the offending agent of post-diarrheal hemolytic uremic syndrome, characterized by glomerular ischemic changes preceding microvascular thrombosis. Because podocytes are highly sensitive to Stx cytotoxicity and represent a source of vasoactive molecules, we studied whether Stx-2 modulated the production of endothelin-1 (ET-1), taken as candidate mediator of podocyte dysfunction. Stx-2 enhanced ET-1 mRNA and protein expression via activation of nuclear factor B (NF-B) and activator protein-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 51 publications
5
106
1
Order By: Relevance
“…This effect is BP independent and is mediated by a direct effect on the cytoskeleton of podocytes. 27,28 Thus, the observed decrease in proteinuria with macitentan might be a direct consequence of renal ET receptor blockade. In addition, BP decreased by 60% during administration of macitentan.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is BP independent and is mediated by a direct effect on the cytoskeleton of podocytes. 27,28 Thus, the observed decrease in proteinuria with macitentan might be a direct consequence of renal ET receptor blockade. In addition, BP decreased by 60% during administration of macitentan.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we showed that only albumin concentrations of 10 -20 mg/ml induce apoptosis in LLC-PK1 cells (8). Then, even though the GSC for albumin is higher than has been proposed, the albumin concentration in the lumen of the PT does not reach the concentration that causes toxic effects on these cells (17,(21)(22)(23). In the present work, we showed that albumin concentrations ranging from 0.001 up to 1.0 mg/ml increased (Na ϩ ϩ K ϩ )-ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cellular responses such as activation of PKB, JAK/STAT, NF-B, and MAPK pathways are triggered by interaction between albumin and megalin (8,17,(22)(23)(24). In the present work, we showed that PI3K/PKB activation is involved in the effect of lower albumin concentrations on PT (Na ϩ ϩ K ϩ )-ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR and quantitative RT-PCR were performed as described previously. 50,51 Primer sequences are shown in Table 1.…”
Section: Rt-pcr and Quantitative Real-time Rt-pcrmentioning
confidence: 99%